Atypical neuroleptic drugs downregulate dopamine sensitivity in rat cortical and striatal astrocytes - Reuss, Bernhard; Unsicker, Klaus (Molecular and cellular neuroscience, 2001)
Psychotic symptoms in different neuropsychiatric disorders are treated by neuroleptic drugs. Neuroleptics are known to block dopamine (DA) neurotransmission, however, cell types mediating their actions have not been determined. Recently, astrocytes have been demonstrated to express D1- and D2-DA receptors, whose activation leads to transient increases in intracellular calcium concentration. We show here that DA-sensitivity of cortical and striatal rat astroglial cultures, as monitored by calcium imaging, is reduced by a 12-h exposure to the atypical antipsychotic agents Clozapine (>1 nmol/liter), Olanzapine (>100 nmol/liter), and Risperidone (>1 nmol/liter), but not by classical neuroleptics Haloperidol and Sulpiride. These effects could not be reverted by the receptor-specific antagonists SCH23390, Sulpiride, L745 870, Ergotamine, and Propranolol. In addition, RT-PCR and Western blot analyses concerning the effects of Clozapine, Olanzapine, and Risperidone on DA receptor expression in cortical and striatal astroglial cells revealed no alterations in mRNAs and immunoreactive protein of D1- and D2-DA receptor subtypes. These results provide the first evidence that atypical but not classical neuroleptic drugs reduce astroglial DA-sensitivity, a mechanism that may be important for a better understanding of differences in effects and side effects between atypical and classical neuroleptic drugs.
Available online 25 May 2002
Gesehen am 13.04.2017